DETERMINAN KUALITAS AUDIT: LOCUS OF CONTROL, INDEPENDENSI, DAN SKEPTISISME PROFESIONAL - Marsya Aulia Purwaningrum (2023)
This study aims to determine the effect of locus of control, independence, and professional skepticism on audit quality. The population of this study is auditor that work at Public Accounting Firms (KAP) in Jakarta. This research is using quantitative research. This study used purposive sampling technique and obtained 50 auditors as respondents. This research data are analyzed using multiple linear regression analysis with significance level of 5%. The results of this study showed that (1) Locus of control has no effect on audit quality, (2) Independence of the auditor has no effect on audit quality, (3) Professional skepticism had a significant and positive effect on audit quality.